Assessment of predictive validity and feasibility of Edmonton Frail Scale in identifying postoperative complications among elderly patients: a prospective observational study - He, Yingke (Sci Rep, 2020)
Frailty is defined as diminished physiological reserve predisposing one to adverse outcomes when exposed to stressors. Currently, there is no standardized Frail assessment tool used perioperatively. Edmonton Frail Scale (EFS), which is validated for use by non-geriatricians and in selected surgical populations, is a candidate for this role. However, little evaluation of its use has been carried out in the Asian populations so far. This is a prospective observational study done among patients aged 70 years and above attended Preoperative Assessment Clinic (PAC) in Singapore General Hospital prior to major abdominal surgery from December 2017 to September 2018. The Comprehensive Complication Index (CCI) and Postoperative Morbidity Survey (POMS) were used to assess their postoperative morbidity respectively. Patient’s acceptability of EFS was measured using the QQ-10 questionnaire and the inter-rater reliability of EFS was assessed by Kappa statistics and Bland Altman plot. The primary aim of this study is to assess if frailty measured by EFS is predictive of postoperative complications in elderly patients undergoing elective major abdominal surgery. We also aim to assess the feasibility of implementing EFS as a standard tool in the outpatient preoperative assessment clinic setting. EFS score was found to be a significant predictor of postoperative morbidity. (OR 1.35, p < 0.001) Each point increase in EFS score was associated with a 3 point increase in CCI score. (Coefficient b 2.944, p < 0.001) EFS score more than 4 has a fair predictability of both early and 30-day postoperative complications. Feasibility study demonstrated an overall acceptance of the EFS among our patients with good inter-rater agreement.